รัฐธรรมนูญและสถาบันการเมือง : ศึกษารัฐธรรมนูญแห่งราชอาณาจักรไทย พ.ศ. 2475 แก้ไขเพิ่มเติม พ.ศ.2495 - อังกูร จิรกิตยางกูร (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
This master thesis aims to analysis the Constitution of the Kingdom of Thailand B.E.2475 as amended by the Constitution amendments B.E.2495 with the political context prior to the announcements, history of this constitution, drafter’s intention, and its enforcement. The conclusion of studying found that the Coup d’état in B.E.2494 was for elimination of constitution B.E.2492 and political institutions power and for the purpose of the constitution B.E.2475 amendment and reannoucement. According to this Constitution, it formed the parliament administration system into a uni-cameral, which had a temporary provision designated the House of Representative to consist of two equally members. The first category member came from direct election and the second category member came from His Majesty the King appointing. Both category members had and equal right and duty. However, the Constitution did not stipulate anyone to be a counter-signature to appoint the second category members. Therefore, practically, the prime minister could propose a list of recognized persons to be entitled to the second category members a purpose of being the government’s power base in the parliament. Due to this constitution, a term of the second category member was 10 years and could not be eliminated by dissolution. The Coup makers, therefore, selected to appoint the military to join the second category member in order to secure the government stability. The Coup makers also wish to handle a fully administrative power by using this constitution as a tool since the Constitution B.E. 2492, which was enforced prior to the revolution did not provide an opportunity for the Coup makers who were the military to accept any position in politic. During the constitution announcement, the government took advantage from the second category member’s existing to control the parliament. Besides, there was a "Legislative Committee", which was set up for accumulate the supporting vote from the first category members by sharing benefit to government supporters. For this reason, executive can fully take over the legislative power. Practically, the parliament rarely be able to proceed its mechanism in examing and balancing the executive power. Moreover, it became a tool and mechanism in the legislation procedures for supporting the executive action. Consequently, there was a conflict between the Coup makers and, later, General Sarit Thanarat did Coup d’etat in September 16, 2500. The following Coup d’etat was arisen on October 20, 2501. As a result, this constitution was, then, revoked. The result derived from studying shows that the Coup makers constitution was aimed to be a political tool in order to gam and maintain the power. By using the Constitution, the Coup makers exercised his Majesty the king’s power through it, created political institutions, and used a military and official power to get rid of their politic opponents. It can be concluded that such constitution brings create advantage to the Coup makers more than Thai civilians.